2023
DOI: 10.3390/ijms241914459
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Oxidative Stress Is the General Reason for Apoptosis Induced by Different-Valence Heavy Metals in Cells and Mitochondria

Sergey M. Korotkov

Abstract: This review analyzes the causes and consequences of apoptosis resulting from oxidative stress that occurs in mitochondria and cells exposed to the toxic effects of different-valence heavy metals (Ag+, Tl+, Hg2+, Cd2+, Pb2+, Al3+, Ga3+, In3+, As3+, Sb3+, Cr6+, and U6+). The problems of the relationship between the integration of these toxic metals into molecular mechanisms with the subsequent development of pathophysiological processes and the appearance of diseases caused by the accumulation of these metals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 353 publications
1
0
0
Order By: Relevance
“…Further, annexin/propidium iodide staining evaluated with FACS analysis indicates a strong increase in both early and late apoptosis upon miconazole 30 µM treatment for 24 h. Under this respect, differences between A375 and SK-MEL-28 may depend on their different growth kinetics. A mitochondrial-dependent apoptosis mediated by caspase3/7 is well known in several pathogenic setups [63][64][65][66], further supporting the role mitochondria play in the antiproliferative effects reported in the present study. Therefore, the collected evidences indicate that miconazole induces apoptosis in melanoma, likely via an early mitochondria disregulation evident at 6 h treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Further, annexin/propidium iodide staining evaluated with FACS analysis indicates a strong increase in both early and late apoptosis upon miconazole 30 µM treatment for 24 h. Under this respect, differences between A375 and SK-MEL-28 may depend on their different growth kinetics. A mitochondrial-dependent apoptosis mediated by caspase3/7 is well known in several pathogenic setups [63][64][65][66], further supporting the role mitochondria play in the antiproliferative effects reported in the present study. Therefore, the collected evidences indicate that miconazole induces apoptosis in melanoma, likely via an early mitochondria disregulation evident at 6 h treatment.…”
Section: Discussionsupporting
confidence: 90%
“…The activation of Cleaved caspase3 serves as a definitive indicator of apoptosis, while the dysregulated equilibrium between the expression levels of anti-apoptotic protein Bcl2 and pro-apoptotic protein Bax can instigate the initiation of the caspase cascade reaction to orchestrate apoptotic processes. 58 Our study confirmed that the activation of Bax by H 2 O 2 , a pro-apoptotic protein in the Bcl2 family, antagonized the anti-apoptotic protein Bcl2, leading to the alteration of the mitochondrial outer membrane permeabilization. This process resulted in the release of cytochrome C, which then promoted apoptosome formation, triggering Caspase-3-mediated substrate degradation and ultimately inducing apoptosis.…”
Section: Discussionsupporting
confidence: 79%